Norms, Incentives and Information in Income Insurance - Assar Lindbeck; Mats Persson (Research Institute of Industrial Economics (IFN), 2015)
In this paper, we ask under what conditions norms can enhance welfare by mitigating moral hazard in income insurance. We point out a particular role of norms, namely to compensate for insurers' difficulties in monitoring the behavior of insured individuals. Thus, the functioning of social norms depends crucially on information, in particular on what norm enforcers are able to observe about an insured individual's behavior. Information is also decisive when distinguishing between social norms and internalized norms. We study how optimal insurance arrangements, the behavior of insured individuals, and welfare are influenced by norms. We also examine the optimal strength of norms. Generally speaking, the paper is a study of the interaction between norms and economic incentives.
Keywords: D82; H55; H75; I13; J22; 330; Norms; Moral hazard; Insurance; Information